2023
DOI: 10.1007/s11089-023-01079-7
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of Externality, Oppression, and Agency: Perceptions of the Role of the Demonic in Mental Illness Among Evangelical Christians

Abstract: Accounts of the demonic within the Christian tradition as causative in differing forms of illness and suffering can be traced back to the New Testament. Demonic accounts also exist more centrally in the language of spiritual warfare that pervades some evangelical groups. Contemporary research suggests that belief in the demonic as aetiologically culpable in mental illness has potentially stigmatising effects for those with mental illness and can also negatively impact help-seeking behaviours. However, no resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…This may offer feelings of empowerment and agency through perceived access to a powerful combative tool over the demonic forces causing mental illness (e.g., Christ, the Holy Spirit and healing prayer; Exline et al, 2021; Wilt et al, 2023). This finding mirrors recent research which has explored social perceptions of the demonic among Christian groups (Lloyd & Panagopoulos, 2023). Demonic etiologies may therefore enhance proximate meaning making by providing an explanation of the source of the suffering along with a sense of hope that the suffering associated with mental ill-health will be alleviated by divine aid (Exline & Wilt, 2023; Lloyd et al, 2023).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This may offer feelings of empowerment and agency through perceived access to a powerful combative tool over the demonic forces causing mental illness (e.g., Christ, the Holy Spirit and healing prayer; Exline et al, 2021; Wilt et al, 2023). This finding mirrors recent research which has explored social perceptions of the demonic among Christian groups (Lloyd & Panagopoulos, 2023). Demonic etiologies may therefore enhance proximate meaning making by providing an explanation of the source of the suffering along with a sense of hope that the suffering associated with mental ill-health will be alleviated by divine aid (Exline & Wilt, 2023; Lloyd et al, 2023).…”
Section: Discussionsupporting
confidence: 86%
“…Specifically, it identified both the helpful and unhelpful factors of this explanatory model. While much literature has focused on the positive (Zagożdżon & Wrotkowska, 2017) and negative outcomes of spiritualized etiologies of mental illness (see Exline et al, 2021; Mercer, 2013; Weaver, 2014), few articles have focused on exploring the positive and more functional outcomes associated with a demonic etiology of mental illness (Lloyd & Panagopoulos, 2023). This study makes an important effort to identify and recognize the diverse experiences of evangelical Christians in relation to mental illness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That being said, an existing body of research has also suggested that religious individuals are possibly less likely to come forward for mental health help when facing psychological difficulties (Lloyd et al, 2021; Lloyd & Kotera, 2021). It has been suggested that religious individuals with fundamentalist beliefs are more likely to see mental illness as the outcome of a poorer relationship with God, sinful living, or demonic activity (Lloyd et al, 2022; Lloyd & Panagopoulos, 2023). Thus, within the context of such a conceptualization of mental illness, there is also evidence of religious stigma toward mental illness, despite the fact that mental illness is found to be reported less prevalently within religious communities.…”
mentioning
confidence: 99%